Protective effects of Cynara scolymus leaves extract on metabolic disorders and oxidative stress in alloxan-diabetic rats - Ben Salem, Maryem (BMC Complement Altern Med, 2017)
BACKGROUND: Diabetes mellitus (DM) is associated with hyperglycemia, inflammatory disorders and abnormal lipid profiles, currently the extracts from leaves of cynara scolymus has been discovered to treat metabolic disorders and has been stated by multitudinous scientists according to a good source of polyphenols compounds. The present study aimed to evaluate the protective effect of the ethanol leaves extract of C. scolymus in alloxan induced stress oxidant, hepatic-kidney dysfunction and histological changes in liver, kidney and pancreas of different experimental groups of rats. METHODS: We determinate the antioxidant activity by ABTS(.+) and antioxidant total capacity (TAC) of all extracts of C. scolymus leaves, the inhibition of α-amylase activity in vitro was also investigated. Forty male Wistar rats were induced to diabetes with a single dose intraperitoneal injection (i.p.) of alloxan (150 mg/kg body weight (b.w.)). Diabetic rats were orally and daily administrated of ethanol extract from C. scolymus at two doses (200-400 mg/kg, b.w) or (12 mg/kg, b.w) with anti-diabetic reference drug, Acarbose for one month. Ethanol extract of C. scolymus effect was confirmed by biochemical analysis, antioxidant activity and histological study. RESULTS: The results indicated that the ethanol extract from leaves of C. scolymus showed the highest antioxidant activity by ABTS(.+) (499.43g± 39.72 Trolox/g dry extract) and (128.75 ± 8.45 mg VC /g dry extract) for TAC and endowed the powerful inhibition in vitro of α-amylase activity with IC50=72,22 ug/uL. In vivo, the results showed that ethanol extract from the leaves of C. scolymus (200-400 mg/kg) decreased significantly (p < 0.001) the α-amylase levels in serum of diabetic rats, respectively associated with significant reduction (p < 0.001) in blood glucose rate of 42,84% and 37,91% compared to diabetic groups after 28 days of treatment, a significant lowered of plasma total cholesterol (T-Ch) by 18,11% and triglyceride (TG) by 60,47%, significantly and low-density lipoproteins (LDL-C) by 37,77%, compared to diabetic rats, moreover, the administration of ethanol extract appears to exert anti-oxidative activity demonstrated by the increase of CAT, SOD and GSH activities in liver, kidney and pancreas of diabetic rats. This positive effect of the ethanol extract from C. scolymus was confirmed by histological study. CONCLUSION: These observed strongly suggest that ethanol extract from the leaves of C. scolymus has anti-hyperglycemic properties, at least partly mediated by antioxidant and hypolipidemic effects.